(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article is about considering sports as not just games and competitions, but the most influential tool and priority task that glorifies the nation’s gene pool, the country’s power and prestige to the whole world, and studying foreign experience. Developed countries such as the USA, Russia, China, England, Japan, South Korea, Germany, France are accumulating vast experience in this field. Studying their experience, comparing them, and taking some of them as examples will help us develop and further improve the field of physical culture in our country. As a result of studying foreign experience, our main goal is to develop women’s sports, form their physical culture, and improve their physical fitness.